PENINGKATAN KEMAMPUAN BERHITUNG ANAK USIA 4-5 TAHUN MELALUI PERMAINAN BALOK ANGKA DI TK HARAPAN BUNDA DESA KUBU KANDANG BATANGHARI - Jamiati; Husin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The formation of early numeracy skills in early childhood requires concrete and engaging learning media. However, abstract mathematical concepts often become obstacles in the learning process, causing children to experience difficulties in recognizing symbols and counting numbers. This study aims to analyze the improvement of early numeracy skills in children aged 4–5 years through the use of number block games in Group B1 at Harapan Bunda Kindergarten, Kubu Kandang Village, Batang Hari Regency. The approach used in this research is qualitative descriptive with a case study design. The research subjects consisted of the principal, classroom teachers, companion teachers, and Group B1 students. Data collection was carried out comprehensively through observation, interviews, and documentation methods. The validity of the research data was tested through extended participation, observation persistence, and data triangulation. The results showed that: 1) The numeracy learning process is carried out through three main stages: planning integrated into the institutional curriculum, RPPM, and RPPH; learning implementation packed through meaningful play activities and routine habituation; and assessment using observation instruments, anecdotal records, and child portfolios. 2) Supporting factors for the success of this method are driven by contextual curriculum content, strong internal school motivation, and the availability of adequate educational game tools (APE) infrastructure. 3) The practical application of number block games is able to eliminate obstacles in early mathematics learning by stimulating children's cognitive functions in symbolic thinking, facilitating the mastery of number symbols one to ten, while providing comfort for teachers in facilitating a concrete and fun learning process.